Urinary dysfunction with detrusor hyperactivity in women with Parkinson's disease cannot be blamed as a factor of worsening motor performance - Raimundo Nonato Campos-Sousa; Elizabeth Maria Aparecida Barasnevicius Quagliato; Kelson James Almeida; Inacio Augusto Dias de Castro; Viriato Campelo (Arquivos de Neuro-Psiquiatria)
Introduction Detrusor hyperactivity is the leading cause of urinary dysfunction in Parkinson's disease (PD). There are few studies correlating PD clinical aspects with this autonomic feature. Methods A cohort of 63 women with PD were prospectively examined for assessment of clinical aspects and disease severity using unified Parkinson's disease rating scale and Hoehn-Yahr scale, respectively. The urologic function was evaluated by the urodynamic study. Two groups were categorized at this time - groups with and without detrusor hyperactivity. After seven years, the same parameters were re-evaluated. Results Progression of the disease on mental scores was found in the group with detrusor hyperactivity. On follow-up, clinical symptoms and severity did not show significant worsening between the groups. Conclusion Detrusor hyperactivity is a frequent urodynamic finding in PD, and even though it is associated with dopaminergic dysfunction, it cannot be blamed as a factor of worsening motor performance, but is probably associated with poor cognitive and mental prognosis.